2016
DOI: 10.1159/000447836
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Hyperglycemia in Fetoplacental Endothelial Dysfunction in Gestational Diabetes Mellitus

Abstract: Background: Gestational diabetes mellitus (GDM) is associated with structural and functional alterations in various tissues including endothelial dysfunction. The aim of this study was to explore the effects of hyperglycemia on fibroblast growth factor 2 (FGF2)- and vascular endothelial growth factor (VEGF)-stimulated placental angiogenesis and the underlying molecular signaling mechanisms. Methods: The density of fetal placental capillaries was examined using immunohistochemistry. Human umbilical vein endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…After this period, cells were pre-treated with 20 µM EA (Sigma Aldrich, St. Louis, MO) and then stimulated with 30 mM high glucose (HG) for 24 hours. Some set of experiments were performed in the presence of PD98059 (10mM, 30 minutes pre-incubation), a potent and selective ERK1/2 inhibitor [35]. As a control, HUVEC were maintained in 5 mM normal glucose (NG).…”
Section: Endothelial Cells Culturementioning
confidence: 99%
“…After this period, cells were pre-treated with 20 µM EA (Sigma Aldrich, St. Louis, MO) and then stimulated with 30 mM high glucose (HG) for 24 hours. Some set of experiments were performed in the presence of PD98059 (10mM, 30 minutes pre-incubation), a potent and selective ERK1/2 inhibitor [35]. As a control, HUVEC were maintained in 5 mM normal glucose (NG).…”
Section: Endothelial Cells Culturementioning
confidence: 99%
“…GDM is considered a prediabetic state, while it shares a series of typical pathophysiological characteristics with type 2 diabetes including insulin resistance, hyperglycemia, biochemical abnormalities, and hyperlipidemia ( Yefet et al., 2019 ). A great number of reports have revealed that the microvascular cell and vascular endothelial cell (VECs) dysfunctions occurred in the umbilical cord and placenta in GDM might lead to immediate or long-term cardiovascular disease risk ( Di Fulvio et al., 2014 ; Sultan et al., 2015 ; Zhou et al., 2016 ; Amrithraj et al., 2017 ). And endothelial dysfunction is a key cause of pathogenesis when pregnancy metabolic disorders occur, including GDM, hypertensive disorders, obesity, and hyperlipidemia ( Echeverria et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that EPCs could be recruited to arterial injury sites and contribute to angiogenesis [6, 7]. However, evidences show that the number of circulating EPCs is reduced and their function is impaired in patients with cardiovascular risk factors, including diabetes [8, 9]. A negative correlation between EPCs and intracellular reactive oxygen species (ROS) production has been proposed [10].…”
Section: Introductionmentioning
confidence: 99%